Methyl Jasmonate Acts as a Crucial Player in Abiotic Stress Responses in Grape - Abdul Hakeem; Shaonan Li; Mustapha Muhammad Nasiru; Ghulam Mustafa; Essam Elatafi; Lingfei Shangguan; Jinggui Fang (Stresses, 2025)
Abiotic stresses are the major factors limiting grape production in the world. They significantly impede grape growth and production. However, during the grape production stage, plant growth regulators play a crucial role in regulating grape developmental progress, especially methyl jasmonate (MeJA). The exogenous MeJA participates in different crop production, gene expression, signaling transduction, natural defense, stress resistance, hormone balance, osmotic regulation, cellular metabolic process, and thermostatic regulation. Grape crop resilience to different abiotic and biotic stresses was overall fascinated by exogenous applications of MeJA. Therefore, in this review, we focus on the MeJA hormone in abiotic stress relief and discovery, application, significance, occurrence, growth via development, stress responses, interaction, molecular modulation, and biological signaling in the grape. Exogenous MeJA in abiotic stress responses explained the physiological change and the signaling pathway has emerged as one of the key plant metabolic processes vs. photosynthetic productivity, playing a substantial role in gene expression, quality parameters, fruit attribution, protein differentiation, cellular programming, and reprogramming, and tolerance mechanism. MeJA hormone has been discovered after a broader study as abiotic stress-responsive methyl jasmonate/Jasmonic acid, which could be a pivotal target not only for grape production but also for other crops.